A review of dipterocarps: taxonomy, ecology and silviculture - Appanah, S.; Turnbull, J.W. (Center for International Forestry Research, 1998)
Dipterocarps are one of the best known and commercially important groups of tropical trees. They preside over some of the most magnificent forest formations in the world. Exploitation of dipterocarp-dominated tropical rain forests has expanded rapidly in the past 20 years. Efforts to develop and implement sustainable management practices are being intensified and there is a pressing need for high quality information on which to base management decisions and reorient research. This book is a critical compilation of the results of research spanning 150 years on the taxonomy, ecology, silviculture and non-timber forest products of these trees. The 13 authors are internationally recognised as specialists in their fields, and the 10 chapters provide comprehensive digests of information and identification of priority research needs.